A coplanar‐waveguide‐fed planar integrated cavity backed slotted antenna array using TE33 mode. Issue 10 (30th June 2020) - Kumar, Arvind; Al‐ Hasan, Mu'ath Jodei
Abstract: This short communication presents a substrate integrated waveguide planar cavity slotted antenna array. The proposed antenna array, excited in its TE33 higher mode, incorporates a grounded coplanar‐waveguide (CPW) CPW‐feeding excitation mechanism. The electromagnetic energy is coupled to the air through 3 × 3 slot array etched on top metallic layer. The proposed antenna operates in the X‐band for the frequency range around the 10 to 11 GHz with resonances at 10.4 and 10.8 GHz frequencies. The proposed antenna array was fabricated and tested. Experimental results show good impedance matching with enhanced radiation characteristics, in terms of peak gain, cross‐polarization level, and low back‐radiation. The proposed antenna has the advantages of low‐footprints, lightweight, high gain, low‐cost, and ease of integration with other electronic circuits. With these characteristics, the proposed antenna array can find its applications in compact wireless digital transceivers.